2007
DOI: 10.1001/archneur.64.7.959
|View full text |Cite
|
Sign up to set email alerts
|

Skin Denervation and Cutaneous Vasculitis in Eosinophilia-Associated Neuropathy

Abstract: Background: Eosinophilia is frequently associated with peripheral neuropathy, and neuropathic pain is a major presentation. Little is known about the involvement of sensory nerve terminals and the vasculature in the skin of patients with eosinophilia. Objectives: To investigate the skin innervation and the pathological abnormalities of the cutaneous vasculature and their clinical significance in eosinophilia-associated neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…These eosinophils are degranulating and cytotoxic to nerves (209, 210). Sometimes eosinophils form part of the inflammatory infiltrate surrounding necrotizing vessels (209, 211, 212). This may accelerate damage of blood vessels because eosinophils were shown to be directly cytotoxic to endothelial cells in vitro (34, 213).…”
Section: Role Of Eosinophils In Autoimmune Diseasesmentioning
confidence: 99%
“…These eosinophils are degranulating and cytotoxic to nerves (209, 210). Sometimes eosinophils form part of the inflammatory infiltrate surrounding necrotizing vessels (209, 211, 212). This may accelerate damage of blood vessels because eosinophils were shown to be directly cytotoxic to endothelial cells in vitro (34, 213).…”
Section: Role Of Eosinophils In Autoimmune Diseasesmentioning
confidence: 99%
“…5,10,[16][17][18][19][20][21] Several studies recently applied IENFD quantification in axonal neuropathy, vasculitic neuropathy, and hereditary neuropathy. [22][23][24] Comparison the IENFD of symptomatic side with that of symmetric healthy side is a useful way to diagnose asymmetric or focal neuropathy. 25 Skin biopsy is a minimally invasive method and repeated biopsy causes no complication.…”
Section: Applications and Limitations Of Ienfdmentioning
confidence: 99%
“…However, no change was observed in 18 diabetic patients after pancreas/kidney transplantation (SPK) (Boucek et al, 2008). Several recent studies have also shown a significant reduction in IENFD in high fat fed mice with moderate hyperglycemia (Chao et al, 2007b;Vincent et al, 2009). These data suggest that IENF loss is an early feature of diabetes, progresses with increasing neuropathic severity, and may improve with appropriate intervention.…”
Section: Diabetic Neuropathymentioning
confidence: 99%